Non-Controlling Minority Shareholdings and Collusion - Samuel de Haas; Johannes Paha (Review of Industrial Organization, 2020)
This article merges theoretical literature on non-controlling minority shareholdings (NCMS) in a coherent model to study the effects of NCMS on competition and collusion. The model encompasses both the case of a common owner holding shares of rival firms as well as the case of cross ownership among rivals. We find that by softening competition, NCMS weaken the sustainability of collusion under a greater variety of situations than was indicated by earlier literature. Such effects exist, in particular, in the presence of an effective competition authority.
Keywords: 330; Collusion; Common ownership; Cross ownership; Minority shareholdings